(untitled) (Revista revoluciones, 2021)
This study had the main objective of answering how much is known about the precautionary principle for environmental problems and how much the precautionary principle applies within its environmental management instruments for environmental problems. Thus, through the analysis of cases, surveys were conducted with mayors, councilors, population, officials, and specialists from specific localities in the Puno region, subsequently carrying out a legal analysis of the application of the precautionary principle to environmental problems in the region. Fist. Of the first results between mayors, councilors and residents no more than 13% and between public officials and specialists 67% to 75% if they know the precautionary principle in both cases related to environmental issues, as a second result it was obtained that among mayors, councilors, population, officials and specialists 97% of the total groups surveyed do not apply the precautionary principle in their environmental management instruments for environmental problems. In the analysis of cases carried out, several application alternatives were found with the aim of reducing environmental pollution and socio-environmental conflicts, but the ignorance of this rule by a large percentage of authorities, officials and the population does not allow it to be used. this legal instrument.